2002
DOI: 10.1067/mtc.2002.120335
|View full text |Cite
|
Sign up to set email alerts
|

Failure of airway healing in an ovine autotransplantation model that includes basic fibroblast growth factor

Abstract: In contrast to the results achieved by other authors with canine models, the neovascularization of tracheal autografts was not achieved in sheep with the topical administration of basic fibroblast growth factor. Cranially pediculated muscular wrapping led to poorer circulation in the tissue around the graft than did no therapy at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In fact, treatment with free-bFGF could not induce sufficient angiogenesis in an ovine tracheal autotransplantation model. 18 This study showed that the biologic effect of bFGF in its free form was limited but that mGHMs/bFGF was effective for angiogenesis, arteriogenesis, or both in vivo. It was further reported that in vivo gene transfection with a growth factor through the pulmonary artery induced angiogenesis in the rat lung.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, treatment with free-bFGF could not induce sufficient angiogenesis in an ovine tracheal autotransplantation model. 18 This study showed that the biologic effect of bFGF in its free form was limited but that mGHMs/bFGF was effective for angiogenesis, arteriogenesis, or both in vivo. It was further reported that in vivo gene transfection with a growth factor through the pulmonary artery induced angiogenesis in the rat lung.…”
Section: Discussionmentioning
confidence: 85%
“…Medial wall thickness was also assessed as the percentage of medial wall thickness by 2 pathologists using elastica van Gieson stain, as described previously. 18…”
Section: Histopathologymentioning
confidence: 99%
“…Behrend et al have reported consistent failure of autografts [15] and allografts [16] in sheep, postulating that tracheal homografts in this animal model undergo necrosis and reabsorption, and are unavoidably destined to be replaced by a fibrous scar. On the other hand, Murakawa et al [17] obtained satisfactory results with noncircumferential transplantation of five rings in primates, but only leaving intact the membranous portion of the host and in a small number of animals.…”
Section: Discussionmentioning
confidence: 92%
“…Many previous studies have mentioned infection as a probable cause of graft failure in the sheep, [3,15,16] and it is possible that this complication is mainly…”
Section: Discussionmentioning
confidence: 96%
“…Some investigators have advocated that bFGF can potentially enhance the blood supply to devascularized trachea in several animal models (33, 48–50). However, other investigators have shown unsuccessful results of tracheal revascularization by means of topical administration of bFGF with muscle wrapping in sheep (51). This is probably due to inadequate dosage of bFGF and gutless revascularization by wrapping materials.…”
Section: Treatment Optionsmentioning
confidence: 99%